ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY RATIO, PRICE EARNING RATIO DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Febdwi Suryani; Selly Erina; Pujiono Pujiono; Helly Aroza Siregar; Suharti Suharti (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this research is to find out the influences of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), Price Earnings Ratio (PER) and Dividend Payout Ratio (DPR) towards the stock prices of automotive and components sector company in Indonesia Stock Exchange (IDX) Period 2014-2018, both partially and simultaneously. Populations on this research is automotive and components sector company which been registered at IDX since period 2014-2018. Data analysis technique used in this research are multiple linear regression analysis, classical assumption test, model test and hypothesis test. The result of the test show that Return on Equity (ROE) has influence on the stock prices, while Current Ratio (CR), Debt to Equity Ratio (DER), Price Earnings Ratio (PER) and Dividend Payout Ratio (DPR) have no influence on the stock prices of automotive and components sector company. Penelitian ini bertujuan untuk mengetahui pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), Price Earnings Ratio (PER) dan Dividend Payout Ratio (DPR) terhadap harga saham pada Perusahaan Sektor Otomotif dan Komponen di Bursa Efek Indonesia (BEI) tahun 2014-2018, baik secara parsial maupun simultan. Populasi dalam penelitian ini adalah perusahaan sektor otomotif di Bursa Efek Indonesia yang terdaftar tahun 2014-2018. Teknik analisis yang digunakan adalah analisis regresi linear berganda, uji asumsi klasik, uji model dan pengujian hipotesis. Hasil pengujian menunjukkan Return on Equity (ROE) berpengaruh terhadap harga saham sedangkan Current Ratio (CR), Debt to Equity Ratio (DER), Price Earnings Ratio (PER) dan Dividend Payout Ratio (DPR) tidak memiliki pengaruh terhadap harga saham pada perusahaan sektor otomotif dan komponen.